Examining young Malaysians travel behavior and expenditure patterns in domestic tourism - Lim, Khong Chiu; Ramli, Kamal Izzuwan; Yusof, Noor Suhaila; Cheah, Swee Ting (Canadian Center of Science and Education, 2015)
Young travellers, though restricted by relatively low levels of disposable income, are commonly having high interest and leisure time in exploring new destinations.It has been found that young travellers have high expectations regarding the importance of value for money though they have their financial resources available for travelling.Therefore, it has raised questions on the worthiness of carrying out a study about the travel behaviour and expenditure patterns among the young travellers in Malaysia.The study employed a survey questionnaire to collect data, which was adapted from standardized measures. A total of 643 respondents, which has been randomly selected in the Northern States of Malaysia were involved in the study.The completed questionnaires were analysed to measure the variables of the study consisted of selected socio-demographic, travel behavior and expenditure patterns.This study found the expenditure patterns of the young travelers vary with regards to the purchase of tourism products. In addition, the results of the study also portrayed the differences of selected travel-related characteristics of young travelers in relation to the purpose of travel.Thus, this study may provide information which will help tourism marketers to develop marketing tools to satisfy and fulfill those young tourists’ needs and understand certain reasons behind their spending patterns.